1999
DOI: 10.1108/eb022831
|View full text |Cite
|
Sign up to set email alerts
|

Negotiation Processes and Outcomes in Prosocially and Egoistically Motivated Groups

Abstract: This experiment examined the effects of motivational orientation (prosocial versus egoistic) on interpersonal trust, negotiation behavior, amount of impasses, and joint outcomes in three‐person negotiations. Students participated in a joint venture negotiation, in which motivational orientation was manipulated by allocating individual incentives (egoistic motive) vs. team incentives (prosocial motive). Results indicated that prosocially motivated negotiators achieved more integrative agreements and fewer impas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 159 publications
(109 citation statements)
references
References 24 publications
4
104
0
1
Order By: Relevance
“…Fortunately, there has been an increasing interest in group negotiations (Beersma and De Dreu, 1999, 2002, 2005Olekalns, Brett and Weingart, 2003;Ten Velden et al, 2007). The findings from this research generally support that variables which have been found to be important in dyads, such as information exchange, accurate perceptions of the negotiation structure, type of procedure, motivation and emotion (Bazerman, Curhan, Moore, and Valley, 2000;Thompson, 1990Thompson, , 1991Thompson, , 2005Thompson et al 1988;Weingart, et al, 1993) are also relevant for groups.…”
Section: Achieving High Quality Outcomessupporting
confidence: 69%
See 1 more Smart Citation
“…Fortunately, there has been an increasing interest in group negotiations (Beersma and De Dreu, 1999, 2002, 2005Olekalns, Brett and Weingart, 2003;Ten Velden et al, 2007). The findings from this research generally support that variables which have been found to be important in dyads, such as information exchange, accurate perceptions of the negotiation structure, type of procedure, motivation and emotion (Bazerman, Curhan, Moore, and Valley, 2000;Thompson, 1990Thompson, , 1991Thompson, , 2005Thompson et al 1988;Weingart, et al, 1993) are also relevant for groups.…”
Section: Achieving High Quality Outcomessupporting
confidence: 69%
“…Intermediate variables were measured with a post negotiation questionnaire. Previous research has measured negotiation behavior either by coding verbal transcripts (Adair, Okumura and Brett, 2001;Pruitt and Lewis, 1975;Weingart et al, 1993) or through self or peer reports (Beersma and De Dreu, 1999;Beersma and De Dreu, 2002). A post negotiation questionnaire was chosen, with self and peer reports, to measure both behaviors and perceptions.…”
mentioning
confidence: 99%
“…instruct participants to maximize own payoff, or joint payoff, e.g. Beersma & De Dreu, 1999. Although it is worthwhile to recall that a meta-analysis on different operationalizations of social value in negotiation research indicated that assessing personality difference or telling people to be prosocial had similar effects (De Dreu, Weingart, & Kwon, 2000).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Likewise, the items of our cooperation measure were adapted from Beersma and De Dreu (1999). After selecting an action in the game, the subjects were provided with the following statements, "I selected my action so that my opponents can depend on me", "I selected my action considering how my decisions affect the welfare of my opponents," and "I selected my action so that my opponents and I received the best joint outcome."…”
Section: Competitive and Cooperative Measuresmentioning
confidence: 99%
“…The items of our competitiveness measure were adapted from Beersma and De Dreu (1999). After selecting an action in the game, the subjects were provided with the following statements, "I selected my action only considering my own welfare," and "I selected my action so that my outcome is relatively better than the outcome for my opponents."…”
Section: Competitive and Cooperative Measuresmentioning
confidence: 99%